Revitalisasi Pendidikan Karakter untuk Membentuk Generasi Berintegritas di Era Modern - Melta Ayunitha; Misbah Misbah; Miftahul Rahmah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the revitalization of character education as a strategic effort to shape a generation with integrity in the modern era, marked by rapid technological advancement and globalization. The objective is to analyze the concepts, strategies, and practices of character education revitalization to address contemporary challenges and foster youth who are not only intellectually capable but also morally and ethically strong. Employing a qualitative approach through literature review and content analysis, the research reveals that holistic integration of character education within the curriculum, supported by active roles of teachers, families, and communities, as well as adaptability to the digital era, is effective in building students’ integrity. Collaborative and contextual revitalization of character education is essential to preserve national values and develop a competitive educational ecosystem amid global challenges.